Tankó Béla filozófiaprofesszor, a debreceni M. kir, Tisza István- Tudományegyetem 1936-37. tanévi rector magnificusa - Mudrák, József (Gerundium, 2019)
Béla Tankó Professor of Philosophy the Rector Magnificus of the Hungarian Royal István Tisza University of Debrecen during the academic year 1936–37. After being a teacher in a secondary grammar school in Saxonpolis (Transylvania) Béla Tankó became the leader of the Department of Philosophy as a professor at the newly established Debrecen University of Arts and Sciences. He managed the Department on the ideas of neo-Kantianism what he learned in Cluj. He also managed the Department of Pedagogy as substitute for some years and hold English lessons as lecturer. He took part in establishing Summer University together with János Hankiss and Rezső Milleker. He was the Rector of the university in the academic year 1936–37 that was the period of the silent development. He was famous for his love of music, he patronized music, and during his rectorate, the University Music Circle was founded and the university received a piano. He died in 1946 after a long professorate not long before his retirement.